Effect of Pseudomonas aureofaiciens & Pseudomonas putida on growth of sorghum biocolor and protect them from infection of Rhizoctonia solani fungi - Hammad Nawaf Farhan; Ashwaq Talip Hameed (مجلة جامعة الانبار للعلوم الصرفة, 2012)
The activity of two bacteria isolates Pseudomonas aureofaiciens & Pseudomonas putida in improving some specific and quantitative characters of Sorghum biocolor and protecting the plant from infection with the fungus Rhizoctonia solani was studied. Complete Randomized Design with three replicates was used in this experiment. The results showed significant higher values of treatments with bacterial isolates in growth percentage, leaf area, height of plant, chlorophyll content and dry weight of shoots. The results also showed significant differences in levels of nitrogen and phosphorus in shoot weight of plant for all treatments which treated with bacterial vaccines. The isolates also improved the studied characters of plants cultured in soil contaminated with Rhizoctonia solani and significantly inhibited the effect of plant pathogen. We concluded from this research it can use bacterial vaccines as new biological technique in improving Agricultural production as Biofertilizers and Biocontrol to inhibit fungi growth on crops.